Insightful agility' the regeneration of the Foundation for Community Work : a case study of a nonprofit organisation in the Western Cape - Fredericks, Beulah (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2006.